Comparison of Proximate Composition of Tuna and Mackerel Protein Hydrolysates for Diet Development in Non-Communicable Disease - Septi Nur Rachmawati; Baiq Dewi Sukma Septiani (Pakis Journal Institute, 2026)
Non-communicable diseases (NCDs) remain the leading causes of death worldwide and are closely associated with unhealthy dietary patterns. This condition highlights the need for comprehensive interventions, including dietary approaches. One strategy to reduce the severity of NCDs is the development of food innovations that can improve diet quality, particularly in terms of palatability, without increasing disease risk. Fish protein hydrolysate (FPH) contains amino acids such as glutamate, which contributes to umami taste and can be utilized as a flavor enhancer to improve food acceptability. This study aimed to compare the proximate composition of FPH derived from tuna (Thunnus sp.) and kawakawa (Euthynnus affinis) as a basis for developing flavor enhancers for NCD dietary management. This study used a laboratory experimental design with a quantitative descriptive approach. FPH was produced through enzymatic hydrolysis using papain, followed by proximate analysis including ash, moisture, carbohydrate, protein, and fat contents. The results showed that protein content was higher in tuna FPH, whereas its moisture content was lower than that of kawakawa FPH. Both samples had low fat and ash contents. All parameters differed significantly between samples (p < 0.05), including ash content (p = 0.014), moisture content (p = 0.019), protein content (p = 0.026), carbohydrate content (p = 0.038), and fat content (p = 0.047). Overall, tuna FPH showed better nutritional characteristics and has potential as a natural flavor enhancer to support dietary management in NCDs.